Antibacterial mechanism and growth-promoting effects of antagonistic strain M1 against Fusarium solani - GE Wenpei, WANG Hongling, CUI Xinran, QIAO Han, ZHANG Li, LIU Na (Zhongguo niangzao)
In this study, using the biocontrol bacterium M1, which had the optimal antagonistic effect against Fusarium solani as the research object, the strain was identified by morphological observation, physiological and biochemical tests and molecular biology techniques. The broad-spectrum antimicrobial efficacy of strain M1 was evaluated using the plate confrontation method. The fermentation products of strain M1 were extracted with n-butanol, and the inhibitory mechanism of M1 against F. solani was explored by measuring mycelial growth and spore germination. Its growth-promoting effects on wheat was verified by pot experiments. The results showed that strain M1 was identified as Bacillus amyloliquefaciens, displaying varying degrees of inhibitory action against five fungi, especially for F. solani inhibition rate reached 48.08%. The fermentation product of strain M1 extracted by n-butanol had significant inhibitory effects on mycelium growth and spore germination of F. solani, with inhibition rates as high as 76.92% and 77.67%, respectively. Strain M1 could significantly damage the cell membrane of F. solani, resulting in accumulation of reactive oxygen species, decreased activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT), and increased malondialdehyde (MDA) content. In pot experiments, the addition of M1 bacterial suspension significantly promoted wheat growth, especially at 15 d and 30 d, the fresh mass of wheat plants increased by 42.46% and 61.72%, respectively.